L'impartition des activités logistiques dans le secteur de la santé: les leçons d'une expérience canadienne1. (10th January 2018) - Beaulieu, Martin; Roy, Jacques; Landry, Sylvain
Abstract: Logistics activities are seen by many healthcare organizations as an opportunity for financial savings. The level of logistics complexity in these organizations may explain the challenges they face in applying solutions common in other industries. This case study of a medical‐supply distribution outsourcing initiative to a logistics services provider by a group of hospitals in a region of Canada helps elucidate this complexity. The objective of this article is to identify the dissonances between various points of view in order to articulate lessons for managers while taking into account the specifics of the healthcare sector. By examining information from several sources, this study shows the necessity of: 1) setting objectives and managing expectations in order to maintain the interest and participation of stakeholders throughout the project; 2) updating internal logistics processes prior to outsourcing; 3) carefully considering a gradual transition phase by ensuring short‐term benefits for both partners; 4) requiring problem‐solving skills as a selection criterion for the logistics services provider to ensure continuous improvement in the performance of the outsourced activity; and 5) developing a governance accountability framework to support problem solving between all parties involved. Copyright © 2018 ASAC. Published by John Wiley & Sons, Ltd.